Biocomputing 2015 2014
DOI: 10.1142/9789814644730_0021
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Genetic Interaction Analysis of Glaucoma Using Expert Knowledge Derived From Human Phenotype Networks

Abstract: The large volume of GWAS data poses great computational challenges for analyzing genetic interactions associated with common human diseases. We propose a computational framework for characterizing epistatic interactions among large sets of genetic attributes in GWAS data. We build the human phenotype network (HPN) and focus around a disease of interest. In this study, we use the GLAUGEN glaucoma GWAS dataset and apply the HPN as a biological knowledgebased filter to prioritize genetic variants. Then, we use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…GJA8 and CRYBA4 are both crystalline lens-associated genes implicated in the formation of cataract. While it is well known that cataracts can contribute to the pathogenesis of angle-closure glaucoma, pathway analyses with GWAS SNPs[ 35 ] have identified associated SNPs in genes CDK4PS , NFYAP1 , and LGMNP1 shared between the POAG and cataract phenotypes, suggesting a potential genetic connection between these conditions. GJA8 has been linked to ocular developmental abnormalities of microcornea[ 36 ] and microphthalmia[ 37 ], both of which may be related to glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…GJA8 and CRYBA4 are both crystalline lens-associated genes implicated in the formation of cataract. While it is well known that cataracts can contribute to the pathogenesis of angle-closure glaucoma, pathway analyses with GWAS SNPs[ 35 ] have identified associated SNPs in genes CDK4PS , NFYAP1 , and LGMNP1 shared between the POAG and cataract phenotypes, suggesting a potential genetic connection between these conditions. GJA8 has been linked to ocular developmental abnormalities of microcornea[ 36 ] and microphthalmia[ 37 ], both of which may be related to glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…All three studies found intriguing relationships between SNP interactions and phenotypes, highlighting potential interactions between gene products while also providing biological context for the interactions behind the identified associations. In a separate study, bipartite networks were used to build a human phenotype network within a glaucoma dataset in which epistatic interactions among prioritized SNPs were identified using a statistical epistasis network [90] .…”
Section: Genetic Variation: Snps To Copy Number Variants Epistasis Amentioning
confidence: 99%
“…Generally, it cannot be cured, but it can be controlled [ 25 ]. Some reported glaucoma interaction networks were based on genome wide association studies (GWAS) [ 26 , 27 ] while others focused on interaction networks from genome wide expression studies (GWES) [ 28 , 29 ] but none have yet been based solely on text mining of the vast swath of PMC literature, where all types of glaucoma studies are covered. Such a network is expected to have a wider coverage than prior efforts because it will not be inferred from a particular type of study but rather from all types of studies related to glaucoma.…”
Section: Introductionmentioning
confidence: 99%